Standard threshold laser versus subthreshold micropulse laser for adults with diabetic macular oedema: the DIAMONDS non-inferiority RCT - Noemi Lois; Christina Campbell; Norman Waugh; Augusto Azuara-Blanco; Mandy Maredza; Hema Mistry; Danny McAuley; Nachiketa Acharya; Tariq M Aslam; Clare Bailey; Victor Chong; Louise Downey; et al. (Health Technology Assessment, 2022)
Background: The National Institute for Health and Care Excellence recommends macular laser to treat diabetic macular oedema with a central retinal subfield thickness of < 400 µm on optical coherence tomography. The DIAMONDS (DIAbetic Macular Oedema aNd Diode Subthreshold micropulse laser) trial compared standard threshold macular laser with subthreshold micropulse laser to treat diabetic macular oedema suitable for macular laser. Objectives: Determining the clinical effectiveness, safety and cost-effectiveness of subthreshold micropulse laser compared with standard threshold macular laser to treat diabetic macular oedema with a central retinal subfield thickness of < 400 µm. Design: A pragmatic, multicentre, allocation-concealed, double-masked, randomised, non-inferiority, clinical trial. Setting: Hospital eye services in the UK. Participants: Adults with diabetes and centre-involving diabetic macular oedema with a central retinal subfield thickness of < 400 µm, and a visual acuity of > 24 Early Treatment Diabetic Retinopathy Study letters (Snellen equivalent > 20/320) in one/both eyes. Interventions: Participants were randomised 1 : 1 to receive 577 nm subthreshold micropulse laser or standard threshold macular laser (e.g. argon laser, frequency-doubled neodymium-doped yttrium aluminium garnet 532 nm laser); laser treatments could be repeated as needed. Rescue therapy with intravitreal anti-vascular endothelial growth factor therapies or steroids was allowed if a loss of ≥ 10 Early Treatment Diabetic Retinopathy Study letters between visits occurred and/or central retinal subfield thickness increased to > 400 µm. Main outcome measures: The primary outcome was the mean change in best-corrected visual acuity in the study eye at 24 months (non-inferiority margin 5 Early Treatment Diabetic Retinopathy Study letters). Secondary outcomes included the mean change from baseline to 24 months in the following: binocular best-corrected visual acuity; central retinal subfield thickness; the mean deviation of the Humphrey 10–2 visual field in the study eye; the percentage of people meeting driving standards; and the EuroQol-5 Dimensions, five-level version, National Eye Institute Visual Function Questionnaire – 25 and Vision and Quality of Life Index scores. Other secondary outcomes were the cost per quality-adjusted life-years gained, adverse effects, number of laser treatments and additional rescue treatments. Results: The DIAMONDS trial recruited fully (n = 266); 87% of participants in the subthreshold micropulse laser group and 86% of participants in the standard threshold macular laser group had primary outcome data. Groups were balanced regarding baseline characteristics. Mean best-corrected visual acuity change in the study eye from baseline to month 24 was –2.43 letters (standard deviation 8.20 letters) in the subthreshold micropulse laser group and –0.45 letters (standard deviation 6.72 letters) in the standard threshold macular laser group. Subthreshold micropulse laser was deemed to be not only non-inferior but also equivalent to standard threshold macular laser as the 95% confidence interval (–3.9 to –0.04 letters) lay wholly within both the upper and lower margins of the permitted maximum difference (5 Early Treatment Diabetic Retinopathy Study letters). There was no statistically significant difference between groups in any of the secondary outcomes investigated with the exception of the number of laser treatments performed, which was slightly higher in the subthreshold micropulse laser group (mean difference 0.48, 95% confidence interval 0.18 to 0.79; p = 0.002). Base-case analysis indicated no significant difference in the cost per quality-adjusted life-years between groups. Future work: A trial in people with ≥ 400 µm diabetic macular oedema comparing anti-vascular endothelial growth factor therapy alone with anti-vascular endothelial growth factor therapy and macular laser applied at the time when central retinal subfield thickness has decreased to < 400 µm following anti-vascular endothelial growth factor injections would be of value because it could reduce the number of injections and, subsequently, costs and risks and inconvenience to patients. Limitations: The majority of participants enrolled had poorly controlled diabetes. Conclusions: Subthreshold micropulse laser was equivalent to standard threshold macular laser but required a slightly higher number of laser treatments. Trial registration: This trial is registered as EudraCT 2015-001940-12, ISRCTN17742985 and NCT03690050. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 26, No. 50. See the NIHR Journals Library website for further project information.